Representation of ‘History and Violence’ in the narration of the postmodern novels : Martin Amis’ Time’s Arrow, J M Coetzee’s Disgrace and Salman Rushdie’s Midnight’s Children - Hossain, Mehruna (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2015.